Electrochemical quartz crystal microbalance analysis of the oxygen reduction reaction on Pt-based electrodes. Part 2 adsorption of oxygen species and ClO4(-) anions on Pt and Pt-Co alloy in HClO4 solutions - Omura, J (Langmuir : the ACS journal of surfaces and colloids, 2014)
To gain deeper insight into the role of adsorbed oxygenated species in the O2 reduction reaction (ORR) kinetics on platinum and platinum-cobalt alloys for fuel cells, we carried out a series of measurements with the electrochemical quartz crystal microbalance (EQCM) and the rotating disk electrode (RDE) in acid solution. The effects of anion adsorption on the activities for the ORR were first assessed in HClO4 and HF electrolyte solutions at various concentrations. In our previous work (Part 1), we reported that the perchlorate anion adsorbs specifically on bulk-Pt, with a Frumkin-Temkin isotherm, that is, a linear relationship between Δm and log[HClO4]. Here, we find that the specific adsorption on the Pt-skin/Pt3Co alloy was significantly stronger than that on bulk-Pt, in line with its modified electronic properties. The kinetically controlled current density j(k) for the O2 reduction at the Pt-skin/Pt3Co-RDE was about 9 times larger than that of the bulk-Pt-RDE in 0.01 M HClO4 saturated with air, but the j(k) values on Pt-skin/Pt3Co decreased with increasing [HClO4] more steeply than in the case of Pt, due to the blocking of the active sites by the specifically adsorbed ClO4(-). We have detected reversible mass changes for one or more adsorbed oxygen-containing species (Ox = O2, O, OH, H2O) on the Pt-skin/Pt3Co-EQCM and Pt-EQCM in O2-saturated and He-purged 0.01 M HClO4 solutions, in which the specific adsorption of ClO4(-) anions was negligible. The coverages of oxygen species θ(Ox) on the Pt-skin/Pt3Co in the potential range from 0.86 to 0.96 V in the O2-saturated solution were found to be larger than those on pure Pt, providing strong evidence that the higher O2 reduction activity on the Pt3Co is correlated with higher θ(Ox), contrary to the conventional view